Mass-loss and silicate production in oxygen-rich AGB stars: current understanding and open questions - Marini, Ester; Tosi, Silvia (Frontiers in Astronomy and Space Sciences, 2025)
AGB stars play a crucial role in the chemical enrichment of the Universe, polluting their host galaxies with gas and dust that reflect the nucleosynthesis processes active during their evolution. Among the dust species formed in the AGB phase, oxygen-rich dust is produced in significant quantities in sources with masses above 4 solar masses, influencing wind dynamics and, consequently, the total dust budget of such stars. In this regard, this manuscript aims to update the reader on some key open questions that still limit the estimation of the role of oxygen-rich AGB stars in the silicate budget of the interstellar medium in galaxies. This is achieved by reviewing previous studies and focusing on the limitations in the description of mass-loss rates and dust yields.